Effectiveness of 12-week Om chanting on reaction time and spatial and verbal memory - Aalasyam Naveen,; Vijay Kumar Sayeli,; Uma Pokala, (Asian Journal of Medical Sciences, 2022)
Background: Chanting Om was reported to increase the blood supply to brain structures involved in cognitive functions and improve cognition. Aim and Objectives: The present study was undertaken to observe the effectiveness of 12-week Om chanting on reaction time and spatial and verbal memory. Materials and Methods: Apparently, healthy volunteers (n=20; nine men and 11 women) who were right-handed and were consenting to participate in the study were recruited in the study. The age range of the subjects was 25–55 years. The intervention group participants were trained for reciting OM with the help of professional yoga instructor for a week days. After a week, they were instructed to assemble at the meditation hall of the institute at sharp 6:30 am every day and recite Om chanting for 20 min. Spatial and verbal memory was assessed using the standard methods explained in the literature that is spatial and verbal memory test. Auditory and visual reaction time was assessed using RT apparatus. Results: Spatial, verbal memory, and reaction time in control and intervention group participants were compared in this study. There was a significant improvement in the spatial memory scores in the intervention group when compared with control group. There was a significant improvement in the auditory reaction time for high and low pitch sounds and also visual reaction time for red and green light in the intervention group when compared with control group. Conclusion: The study results explain significant improvement in the spatial and verbal memory scores and auditory and visual reaction time after the intervention. The study recommends further detailed studies to support practicing Om chanting for the well-being of general population.